Peningkatan Kemampuan Muhādatsah di Prodi Pendidikan Bahasa Arab : Perspektif Mahasiswa - Ja’alna Salwinur Baeha; Lola Irnis Lorenza; Andini Rahmawati; Sahkholid Nasution (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Improving the ability of speaking in Arabic Language Education Study Program is an important aspect in the Arabic language teaching process. Speaking skills are one of the main competencies that students must have, both in academic and social contexts. However, learning to speak in Arabic often faces various challenges, such as fear of public speaking, lack of motivation, and limited opportunities to practice. The purpose of this study is to explore the improvement of Arabic speaking skills from the perspective of students by analyzing various methods applied in learning to speak. The research method used is a qualitative method. The data collection techniques in this study used interview and literature study techniques. Interviews were conducted with informants who were students of the Arabic Language Education Study Program. The literature study technique was used with the aim of reviewing and analyzing various literature related to improving the ability of speaking in Arabic Language Education Study Program. The results of the study indicate that the development of more varied learning methods and providing space for students to practice speaking intensively are very important in supporting the improvement of their speaking skills. For that reason, it is important for the study program management to continue to innovate in creating methods and environments that can encourage students to be more active and confident in speaking Arabic.